Changes in oral health-related quality of life after treatment of molar incisor hypomineralization using Glass Hybrid Restorations - Tugcu, Nihan; Sezer, Berkant; Caliskan, Cansu; Durmus, Basak; Kargul, Betul (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the changes in children’s oral health-related quality of life following the treatment of severely affected molar-incisor hypomineralisation with Glass Hybrid Restorative System (GH) after selective caries removal. Method: The observational cross-sectional study was conducted at the Marmara University, School of Dentistry, Department of Pediatric Dentistry. Children aged 11–14 years (n = 55) who were diagnosed with MIH and had finished their dental treatment from November 2018 to December 2019, were included. The children’s MIH-affected teeth were treated with GH after SCR. Participants answered the Child Perceptions Questionnaire (CPQ) prior to their dental treatment and 6 months after the treatment. Results: Of the fifty-five patients, 40 patients (24 girls-16 boys) completed baseline and follow-up data. The mean age of the children was 11.85 (±1.02) years. The overall CPQ score ranged from 3–83 (average 33.27 ± 16.46) at baseline and 0–61 (average 11.67 ± 11.21) at follow up. The emotional well-being among children was the highest score at baseline. A significant decrease (p < 0.001) in the mean values was observed for both the overall CPQ scores and for the scores of the oral symptoms, functional limitations, and social-emotional well-being limitation. All subdomains showed large effect sizes and oral symptom limitation domain presented the greatest effect. Wilcoxon Rank test was used to determine the statistical significance of the changes and the magnitude of change was determined by calculating and classifying the effect size. Conclusion: Restorative treatment with GH following selective caries removal positively influenced the oral health-related quality of life of children with severe molar-incisor hypomineralisation. Key Words: Health-related quality of life, Dental enamel hypoplasia, Questionnaires, Child, Oral health.